PROSES PELAKSANAAN EVENT ROADSHOW NONTON BARENG FILM PETUALANGAN SHERINA 2 BERSAMA INDOFOOD OLEH PT KREASI KARYA BANGSA - Sugiyanto, Shabrina Mitsalina; Sudarno, Sudarno (Bisnis Event, 2024)
Roadshow Event “Nonton Bareng Film Petualangan Sherina 2," organized by PT Kreasi Karya Bangsa (United Creative) for PT Indofood CBP Sukses Makmur, Tbk., integrates brand activation, enhances brand awareness, and demonstrates effective corporate event and roadshow event management. This initiative revives the nostalgic impact of the iconic film "Petualangan Sherina" on Indonesian childhoods, offering consumers, Indofood employees, and various local film and arts communities in Jakarta, Bandung, and Surabaya the opportunity to experience "Petualangan Sherina 2" with Indofood. The event includes pre-event activities such as Instagram giveaways by Indofood, Indomilk Susu Steril, and Chiki Twist, promoting brand awareness and introducing Indofood's new products. Additionally, it features meet & greet sessions with the cast, interactive games with e-wallet prizes, and engaging mascots, enhancing participant engagement and satisfaction. Effective event planning by PT Kreasi Karya Bangsa ensures smooth execution, positive participant feedback, and strengthens client trust, underscoring the importance of meticulous event management in achieving successful brand activations and corporate events.